Analysis of influencing factors on axial compression performance of BFRP bars-coral reef and sand concrete columns. (November 2022) - Junyan, Dai; Shiping, Yin
Abstract: A more systematic analysis of the factors influencing the axial compression performance of basalt-fiber-reinforced polymer (BFRP) bars-coral reef and sand concrete (CRSC) columns was carried out based on axial compression load capacity tests on 15 columns in 5 groups. The test study factors include the concrete strength, longitudinal bars diameter, stirrup spacing, slenderness ratio and bars type, and type of bars material. The results show that the damage process of BFRP bars-CRSC columns can be divided into elastic stage, cracked stage and damage stage. Under different diameters of longitudinal bars, increasing the diameter of longitudinal bars leads to the reduction of the adhesion between longitudinal bars and concrete protective layer, which reduces the load-bearing capacity; decreasing the spacing of hoop bars helps to improve the ductility of the member, but it also reduces the continuity of CRSC and the strength.